KNOWLEDGE SHARING PRACTICES IN LEARNING ENGLISH LITERATURE VIA WHATSAPP - Movi Riana Rahmawanti (Fakultas Keguruan Ilmu Pendidikan Universitas Ibn Khaldun Bogor, 2017)
When it comes to English Literature Classes, sometimes students? find it very hard to understand the materials. Practices of sharing knowledge between teacher and students or between their peers became alternative solution to overcome these difficulties. This study tries to explore students? responses toward knowledge sharing practice in learning English literature through WhatsApp. This is a descriptive qualitative study that uses Forum Group Discussion as the instrument. The participants of this research are 10 students that currently enrolled in literature subject. It can be concluded from the study that although most of the students thought that literature subject is quite difficult, but it is still challenging to them. In relation to Knowledge sharing practices via WhatsApp clear some confusions faced by the students in literature subject.